Nanostructured CeO2/MgAl-LDH composite for visible light induced water reduction reaction. (14th December 2016) - Nayak, Susanginee; Parida, K.M.
Abstract: Exploiting to enhance the visible light harvestation ability of MgAl-LDH, CeO2 have been dispersed over the surface of MgAl-LDH to design a series of CeO2 (x%)/MgAl-LDH composite photocatalyst for visible light induced water reduction reaction. The synthesis of these composites were carried out by using a combination of coprecipitation and hydrothermal route while varying the molar ratio of Ce(NO3 )3 ·6H2 O with respect to MgAl-LDH at constant pH of 10.5. The structural, optical and morphological correlations of these materials were successfully investigated by various physico-chemical techniques. The result signifies tuned-in band gap energy of composites within the range of MgAl-LDH to pure CeO2 i.e. from 3.2 eV to 2.80 eV. Moreover, the role of these composite in visible light induced H2 energy production was well discussed. Among these composites, CeO2 (5%)/MgAl-LDH showed a H2 evolution rate of 990.0 μmol 2 h −1 under visible light irradiation and was enhanced by ca. 1.98 times than pure CeO2 . The HRTEM image demonstrates the formation of hexagonal plates of MgAl-LDH uniformly distributed with the nanorods of CeO2 . The existence of nanorods of CeO2 decreases the charge recombination rate and makes an easy transfer of effective surface charge to the surface of the MgAl-LDH, which facilitates the production of clean H2 . The significant quenching of PL peak and enhancement of photocurrent responses in photocurrent measurement of CeO2 (x%)/MgAl-LDH composites reveals the better separation of electron and hole pairs. Furthermore, a detailed mechanism for the enhanced photocatalytic activity and the synergistic effect played by both MgAl-LDH and CeO2 were also discussed. Graphical abstract: Formation of CeO2 nanorod over the hexagonal platelates of MgAl-LDH cultivate the visible light harvestation ability MgAl-LDH and makes an easy charge separation and transfer in CeO2 (x%)/MgAl-LDH composite materials, which contributes its potential towards the photocatalytic hydrogen evolution under visible-light irradiation. Highlights: Nanostructured CeO2 /MgAl-LDH composite was synthesized by combination of coprecipitation and hydrothermal route. The CeO2 /MgAl-LDH composites possess band gap tuning within the range of MgAl-LDH to pure CeO2 i.e. from 3.2 eV to 2.80 eV. The morphology of CeO2 nanorod and hexagonal plates of MgAl-LDH drives the photocatalytic water reduction reaction. The CeO2 (5%)/MgAl-LDH composite shows the highest H2 production rate of 990.0 μmol 2 h −1 under visible light irradiation.